2009
DOI: 10.1097/brs.0b013e3181abc150
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent Vertebral Body Fracture Following Vertebroplasty With Polymethylmethacrylate or Calcium Phosphate Cement

Abstract: New vertebral fractures occurred at the vertebra adjacent to augmented vertebrae in the P group and in the augmented vertebrae in the C group. The difference in the fractured site may be because of the difference in strength between the 2 bone filler materials. Therefore, the strength of bone filler materials is considered a risk factor in developing adjacent vertebral body fractures after VP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…Of concern is the increased risk of adjacent vertebral body fractures observed in clinical [4,5] and experimental studies [6][7][8]. Although a recent randomized controlled trial comparing vertebroplasty to conservative treatment [9] found no significant difference in adjacent-level fracture incidence, clinically used poly-methyl-methacrylate (PMMA) cements caused marked changes in load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Of concern is the increased risk of adjacent vertebral body fractures observed in clinical [4,5] and experimental studies [6][7][8]. Although a recent randomized controlled trial comparing vertebroplasty to conservative treatment [9] found no significant difference in adjacent-level fracture incidence, clinically used poly-methyl-methacrylate (PMMA) cements caused marked changes in load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of cement in addition to PMMA have also been developed for augmentation. In comparison with PMMA, calcium phosphate cement, for example, leads to fewer adjacent fractures in biomechanical studies, although, the rate of recurrent fractures in the augmented vertebrae themselves is still very high [58]. The use of completely different augmentation materials, such as silicone, instead of cement to achieve better stiffness parameters is new, however.…”
Section: Discussionmentioning
confidence: 99%
“…Vertebroplasty, however, has gained increasing popularity over the last two decades acting in both preventative and therapeutic capacities. Vertebral augmentation with bone cement-most commonly polymethylmethacrylate (PMMA)-has provided early clinical improvement in regard to pain relief in more than 90% of cases [13] (Figure 5). Biomechanically, it serves to retain the normal vertebral and spinal geometry by increasing the VB stiffness and strength.…”
Section: Vertebroplastymentioning
confidence: 99%
“…But the procedure is not without risk. PMMA goes through an exothermic reaction which can cause neurological damage, localized inflammation and osteonecrosis [13] . There are also concerns regarding cement leakage, which can encroach into the spinal canal with disastrous consequences [3] .…”
Section: Vertebroplastymentioning
confidence: 99%